PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN BPJS KESEHATAN KOTA PAREPARE - Farida, Farida; Muhammad Naim (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to analyze the effect of training and career development on the performance of BPJS Health employees in Parepare City. The samples used in this study were 53 BPJS Health employees. The method in this study was quantitative and the data collection techniques used in this study were observation and questionnaires. analyzed by SPSS. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that: (1) Training has a significant positive effect on the performance of BPJS Parepare, (2) Career Development has a significant positive effect on the performance of BPJS Parepare, (3) Training and Career Development together have an effect on the positive and significant impact on the Performance of BPJS Parepare.